Studies on Gripopterygidae (Plecoptera) from Espírito Santo State, Brazil - Gonçalves, Maísa De Carvalho; Novaes, Marcos Carneiro; Salles, Frederico Falcão (Zootaxa, 2017)
Specimens of Gripopterygidae (Plecoptera) from Espírito Santo State and surrounding areas in the state of Minas Gerais, southeastern Brazil, were studied. A new species, Gripopteryx caparao n. sp. is described. The female of Paragripopteryx intervalensis Bispo & Lecci 2011 is described and recorded for a new site. Comments on G. garbei Navás 1936 are presented. New state records are provided for G. cancellata (Pictet 1841), G. reticulata (Brauer 1866), G. juetah Froehlich 1990, G. pilosa Froehlich 1990, P. egena Froehlich 1994, P. intervalensis Bispo & Lecci 2011, P. klapaleki Enderlein 1909, and Tupiperla gracilis (Burmeister 1839).